Factors of Building and Developing an Academic Career: Systematic Theoretical Analysis - A. V. Pesha (Moscow Polytechnic University, 2023)
The paper presents the results of a theoretical with elements of empirical research aimed at identifying the key factors of building an academic career, disclosed in the works of sci- entists with a proposal to visualize the construct of multifactorial conditionality of career growth in the academic environment. The study was conducted on the basis of a systematic bibliographic analysis of the most cited works on the topic, published in the Scopus and RSCI abstract databases, from an empirical point of view. The method of analyzing the digital footprint in online systems for collecting data on the scientific competitions winners (the results of the RNF competitions for 2021, n=146 projects), narrative interview and written survey of university teachers to clarify the moti- vation and awareness of their choice of academic career (n=52 people). The conducted research allows us to form a model of key factors in the development of an academic career, including 4 main, equivalent groups - personal, reputational, systemic factors and factors of social capital, as well as the luck factor, which is highlighted in a number of studies as influencing the quality and speed of building a career trajectory in the field under study. The paper suggests that the development or stagnation of one group of factors will lead to similar movements in other groups. As a result, the author actualizes the use of career lift technology, which taking into account the indicated factors of influence on academic career development indicators, will contribute to the involvement of young people in science and teaching.